A Siyasah Syar‘iyyah Approach To Financial Support Obligations Of Biological Fathers For Illegitimate Children - Nur Alia Batrisyia Rosdi; Ain Syazwani Mohd Kamarulzaman; Nur Izzah Mohamad Fadli; Puteri Nuraniqah Irdina Osmara; Mohd Harifadilah Rosidi (Research and Scientific Innovation Society (RSIS), 2025)
The rise in births of children out of wedlock poses a significant social challenge within Malaysia’s Muslim community. Official data from the National Registration Department indicates that 67,628 illegitimate children were registered between 2020 and October 2024, reflecting the critical scale of the issue and its implications for the country’s social fabric and future human capital development. Illegitimate children, born outside valid marital unions, often face complex legal and socio-economic difficulties. This study examines the obligation of financial maintenance (nafkah) for such children, focusing on the biological father’s role as prescribed by Islamic law, relevant scholarly opinions, and Malaysian legal provisions. Employing a qualitative approach, the research analyses these issues within the framework of Siyasah Shar‘iyyah, Islamic governance principles emphasising public interest (maslahah). The findings highlight the necessity of re-evaluating traditional legal interpretations to address contemporary social realities better, advocating for a balanced approach that safeguards the welfare of illegitimate children while upholding Islamic legal integrity. This study contributes to the ongoing discourse on family law reform and social justice in Islamic contexts, offering recommendations to strengthen legal and moral frameworks for child maintenance obligations.